ANALYSIS OF USER SATISFACTION ON SRIKANDI APPLICATION AT THE SECRETARIAT GENERAL OF REGIONAL REPRESENTATIVE COUNCIL REPUBLIC OF INDONESIA - Safira Salsabilla; Retna Hanani (Journal of Management and Public Policy, 2026)
This Study aims to analyze the user satisfaction of the SRIKANDI application at Secretariat General Regional Representative Council at Secretariat General of the Regional Representative Council Republic of Indonesia. The implementation of the SRIKANDI application is part of the government's effort to support digital archive management and improve administrative efficiency in public institutions. During the adaptation of the application still needs to be improved from several aspects. This Research applies quantitative approach using the End User Computing Satisfaction (EUCS) model. The data were collected through an online questionnaire from 85 respondents and analyzed using PLS-SEM. The analysis result show that three variables, which content, Format, and Timeliness are influences the user satisfaction of the SRIKANDI application. Meanwhile, the variables of accuracy and ease of use do not show a significant influence on user satisfaction. These findings of the study suggest and recommend to improving the the quality of documents uploaded to be more organized and properly managed by classified, improving the interface of the application, upgrade the server capacity and conducting regular system maintenance.